Perencanaan Pengembangan Wellness Tourism di Kawasan Deyangan, Kecamatan Mertoyudan, Kabupaten Magelang - Kristiadi, Didik; Subroto, Yoyok Wahyu; Cemporaningsih, RR. Esti; Mayani, Melati; Fauzia, Tasnim Arma; Ramadhan, Muhammad Alfian; Izzati, Felia (JURNAL NASIONAL PARIWISATA, 2026)
Borobudur Super Priority Tourism Destination requires supporting tourist attractions in its surroundings so that tourists can get experiences and alternative attractions that can extend the length of stay of tourists, so the objectives of this study are 1) Identifying the important value of tourist attractions in the Deyangan area; 2) Describe the prospects for developing tourist attractions in the Deyangan area as wellness tourism; 3) Formulate a strategy for developing wellness tourism products in the Deyangan area; 4) Prepare a site plan for priority areas for developing wellness tourism in the Deyangan area. This study uses a qualitative approach with a case study type using data collection techniques including literature studies, observations, in-depth interviews, and focus group discussions (FGD). The Deyangan area has an important value because it is included in the Borobudur-Yogyakarta-Prambanan integrated development area cluster so that the potential in this area is developed to support the Borobudur tourist attraction. This area has the potential to be developed with the concept of wellness tourism to extend the duration of stay of tourists and increase tourist spending by providing alternative attractions, especially for middle- and upper-class tourists. Wellness tourism product development strategy in Deyangan Area through utilization of site potential adjacent to Progo River and local cassava products. These tourism products are accommodated in an appropriate site design.